Influence of Corrosion on Lifespan of Reinforced Concrete Structures: A Comprehensive Review - Sahani, Kameshwar; Khadka, Shyam Sundar; Sahani, Suresh Kumar (Kathmandu University Journal of Science, Engineering and Technology, 2024)
Carbonation-induced corrosion is a major concern for reinforced cement concrete (RCC) structures, impacting their long-term durability and structural integrity. This review synthesizes the findings on the deterioration mechanisms in concrete structures, focusing on carbonation, chloride-induced corrosion, and time-dependent deterioration. The analysis includes discussions on predictive likelihood methods for estimating bridge reliability, the impact of environmental factors on carbonation, and standardized testing methods for assessing concrete durability. The review highlights the importance of understanding material characteristics and environmental conditions in designing durable concrete structures, emphasizing the processes of carbonation, its impact on rebar corrosion, and strategies for mitigation. Sheltered concrete carbonation resistance in metropolitan tropical climates is 10-20% lower than open exposure. SCM concretes exhibit equivalent or greater long-term carbonation resistance to OPC concretes, as evidenced by the increase in carbonation depth ( Δ xd) at ages greater than 5 years. The paper concludes with recommendations for integrating advanced modeling techniques and empirical studies to develop robust maintenance strategies and improve concrete mix designs for enhanced durability.